Motto ‘Tong Ngin Fan Ngin Jit Jong’ in Harmonization Life Public Malay and Chinese on Bangka Island - Damiasih Damiasih; Ropa Riana (Universitas Mataram, 2022)
Culture and harmonization between two ethnic groups, namely Malay and Chinese on Bangka Island, are commonplace for local people on Bangka Island. The harmonization of the Malay and Chinese people of Bangka gave rise to the term